Peran Guru PAI dalam Pendidikan Karakter untuk Membentuk Moral Siswa di SMPN 2 Tilatang Kamang Kabupaten Agam - Sifatun Shakdiyah; Alimir (YASIN, 2026)
Although character education through Islamic Religious Education learning has been widely studied, research comprehensively examining the role of Islamic Religious Education teachers in shaping students’ morals through the inculcation of religious values, moral guidance, exemplary conduct, and the identification of supporting and inhibiting factors in a junior secondary school context shaped by local culture remains limited. This study aims to analyze the role of Islamic Religious Education teachers in character education to shape students’ morals at SMP Negeri 2 Tilatang Kamang, Agam Regency. This study employed a qualitative approach with a case study design. The research participants comprised the principal, Islamic Religious Education teachers, homeroom teachers, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results showed that Islamic Religious Education teachers played a strategic role in shaping students’ morals through the inculcation of religious values, the provision of moral guidance, exemplary conduct, and the reinforcement of the school’s religious culture. The implementation of these roles was supported by the principal’s leadership, collaboration among educators, and a conducive school culture but faced challenges arising from peer-group influences, social media use, limited parental supervision, and differences in students’ characteristics. These findings affirm that shaping students’ morals requires the integration of religious instruction, teachers’ exemplary conduct, and a supportive educational environment. This study contributes to the development of Islamic Religious Education scholarship concerning the strategic role of teachers in character education and implies the need to strengthen collaboration among schools, families, and communities to support the sustainable moral development of students.